Intrathoracic gossypiboma presenting 47 years later as a purulent fistula: a case report - Shahab Rafieian; Matin Vahedi; Javad Sarbazzadeh; Hesam Amini; Reza Ershadi (Surgical Case Reports, 2022)
Abstract Background Intrathoracic gossypiboma is a consequence of retained sponge/swap, gauzoma, muslinoma, textiloma, or cottonoid in the thoracic cavity during surgery. The thoracic cavity is of the rarest place for gossypiboma as these entities most occur after abdominal surgery. Case presentation We report a case of intrathoracic gossypiboma that was missed for an extended period of time with no symptoms and was successfully treated with surgical intervention. Conclusions The rarity of gossypiboma necessitates a high index of suspicion for correct diagnosis. Gossypiboma is often difficult to diagnose, leading to misdiagnosis and unnecessary interventions. It is important to consider this entity as a diagnosis in any case with an unexplained or unusual presentation during the postoperative period.